Ultrafast laser excited nonlinear optics : harmonic generation and up-conversion luminescence at lanthanide doped up-conversion nanoparticles - Gao, Yi (2019)
Nonlinear optical harmonic generation and lanthanide-ion doped up-conversion (UC) luminescence have been considered as the two main promising candidates to convert low energy photons to high energy ones. Despite their attractive applications in laser development, sub-diffraction limit focusing and bio-imaging, they both suffered from low conversion efficiency. To fulfill their application potential, it is necessary to further understand these phenomena and the interaction between them. In this thesis, nonlinear optical harmonic generation from different substrates was comprehensively characterized to pave ways for precise wafer characterization; a non-invasive inspection technique for inter-layer defects in silicon (Si) wafers with high depth resolution was presented to demonstrate the significant application potential of UC processes in semiconducting industry; the interaction between lanthanide-ion based up-conversion luminescence (UCL) and third harmonic generation (THG) was investigated for coherent enhancement of optical harmonic generation, which will be beneficial in the development of highly efficient coherent UC platforms for ultrafast lasers development and deep ultra-violet (UV) ultrafast pulses generation. This study starts from the characterization of third-order harmonics excited from crystalline sapphire wafers of different cutting planes using femtosecond (fs) laser. The efficiency, optical yield, crystalline orientation and excitation depth dependence were thoroughly characterized. It was found that the crystal orientation affects the THG intensity by ~20% for A, M and R-plane cut wafers, while this orientation dependency was not clear for the C-plane. The maximum excitation depth of THG was found to be 54 μm, and the propagation vectors of third harmonic (TH) and fundamental beam were found to be the same but can be separated. Based on these findings, a demonstration was made to apply optical harmonic generation as a tool for non-contact, non-destructive detection of internal and inter-layer defects in Si wafers with high depth resolution of 121 nm, together with characterization of THG and fifth harmonic generation (FHG) from Si wafers. It was discovered that a modulation depth of 35% and 50% can be achieved for THG and FHG from Si wafers by changing the polarization state of incident laser, and the effective excitation depths of THG and FHG in Si wafer were 20 and 5 μm, respectively. With a better understanding of nonlinear optical harmonic generation, the interaction between THG and lanthanide-ion doped UC nanoparticles (UCNPs) was studied by depositing a thin-film of UCNPs onto either amorphous or single crystalline substrates. Enhancement of THG intensity by 7.8 was discovered when UCNP thin-film was coated on top of substrate. The amplification of THG was believed to be caused by the simultaneous resonance among energy band gap in lanthanide ions, incident laser, and THG.